2015
DOI: 10.3168/jds.2014-9112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of energy density in close-up diets and postpartum supplementation of extruded full-fat soybean on lactation performance and metabolic and hormonal status of dairy cows

Abstract: This experiment was conducted to investigate the effect of energy density (ED) in the close-up period and supplementation of extruded full-fat soybean (ESB) during the first 4 wk after parturition on intake, body weight (BW), metabolic status, and performance of dairy cows. Fifty-seven Chinese Holstein cows with similar parity, previous 305-d milk yield, and expected calving date were dried off at -60 d relative to parturition and fed the standard herd dry-cow diet until -21 d relative to parturition. Energy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
22
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 52 publications
10
22
4
Order By: Relevance
“…BCS, serum glucose, NEFA, and T‐Cho concentrations, and serum AST activities were within the standard values for the dry period reported by Kida (). In addition, the changes in plasma concentrations of insulin and leptin, and the serum concentrations of BHB (Zhang, Su, Wang, Cao, & Li, ) and Alb (Kawashima et al, ) during late gestation were within approximately the same ranges as reported previously. Therefore, the herd examined in the present study appeared to have normal levels of the selected metabolites.…”
Section: Resultssupporting
confidence: 81%
“…BCS, serum glucose, NEFA, and T‐Cho concentrations, and serum AST activities were within the standard values for the dry period reported by Kida (). In addition, the changes in plasma concentrations of insulin and leptin, and the serum concentrations of BHB (Zhang, Su, Wang, Cao, & Li, ) and Alb (Kawashima et al, ) during late gestation were within approximately the same ranges as reported previously. Therefore, the herd examined in the present study appeared to have normal levels of the selected metabolites.…”
Section: Resultssupporting
confidence: 81%
“…Offering concentrates in addition to a grass silage-based diet during the 4 wk prepartum resulted in a higher prepartum total DMI (P < 0.001; Figure 1a) and lower prepartum silage DMI (P < 0.001; Table 3), in agreement with others (Keady et al, 2001;McNamara et al, 2003b). Similarly, offering a more energy-dense TMR during the close-up prepartum period has also been shown to increase prepartum DMI compared with offering less energy-dense diets (Holcomb et al, 2001;Rabelo et al, 2003;Zhang et al, 2015). A treatment × parity interaction was present for total DMI prepartum (P = 0.014), with the respective values for cows and heifers being 11.2 and 8.9 kg/cow per d for SO and 15.0 and 10.0 kg/cow per d for S+C.…”
Section: Prepartum Intake Energy Balance and Body Tissue Changessupporting
confidence: 77%
“…Offering higher energy TMR diets for the entire prepartum period (in cows with a BCS >3.2 at study commencement; scale 1 to 5) resulted in greater body tissue mobilization postpartum (Janovick and Drackley, 2010), and decreased prepartum neutrophil phagocytosis (Graugnard et al, 2012), compared with those offered lower energy rations. Similarly, increasing energy allowance during the last few weeks prepartum (in cows with a mean BCS of 3.2 to 3.5 at study commencement; scale 1 to 5) resulted in a greater degree of negative EB postpartum (Hayirli et al, 2011), higher incidence of subclinical ketosis postpartum (Vickers et al, 2013), and higher serum NEFA concentrations postpartum (Zhang et al, 2015). Thus, when an increased energy allowance is offered to prepartum cows that already are in high BCS, or when this increased energy allowance results in a high BCS, detrimental consequences may ensue.…”
Section: Introductionmentioning
confidence: 99%
“…In pre-calving period, the increased TDMI and CDMI with increasing concentrate supply from Low to High treatment was in agreement with the findings of previous studies (Galic. 2017;Zhang et al, 2015). The increasing nutrient density of the diet with the increasing ratio of concentrate from Low to High resulted in increased TDMI (Singh et al, 2003).…”
Section: Dry Matter Intakementioning
confidence: 99%